2000
DOI: 10.1021/jp0012146
|View full text |Cite
|
Sign up to set email alerts
|

Product Energy and Angular Momentum Partitioning in the Unimolecular Dissociation Of Aluminum Clusters

Abstract: A previous classical trajectory simulation showed that the unimolecular decompositions of Al 6 and Al 13 are intrinsically RRKM. In the work presented here, this study is further analyzed to determine the Al 5 + Al and Al 12 + Al product energy distributions, which are compared with the predictions of statistical theories. Orbiting transition state/phase space theory (OTS/PST) gives distributions in excellent agreement with the trajectory results. Assuming a loose, product-like transition state gives a lower a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 57 publications
3
30
0
Order By: Relevance
“…If the influence of the rotational angular momentum on the fragmentation probabilities can be verified and quantified, for example, along the lines of Refs. [29,30], this may open up the possibility to determine the amount of angular momentum carried by isolated clusters and to investigate the cooling of their rotational degrees of freedom.…”
Section: Discussionmentioning
confidence: 99%
“…If the influence of the rotational angular momentum on the fragmentation probabilities can be verified and quantified, for example, along the lines of Refs. [29,30], this may open up the possibility to determine the amount of angular momentum carried by isolated clusters and to investigate the cooling of their rotational degrees of freedom.…”
Section: Discussionmentioning
confidence: 99%
“…A useful alternative technique lies in statistical rate theories, which can be quantitative provided that anharmonicities are accounted for. 9,11 Here we use the Weisskopf approach from nuclear physics, 41 which is of comparable accuracy as phase space theory for non-rotating systems. 10 According to this theory, the dissociation rate k X corresponding to the emission of X particles can be cast as 10,41 …”
Section: Statistical Dissociationmentioning
confidence: 99%
“…Thermal dissociation of finite clusters offers such an opportunity, as the related observables of rate constants or kinetic energy released are intimately connected to the statistical properties through the densities of states (DOSs). 8,9 Earlier investigations on small rare-gas 9, 10 or metallic 11 clusters have shown that statistical rate theories can be made accurate against numerically exact molecular dynamics simulations if the densities of states are carefully evaluated including anharmonicity effects. In those works, the residual discrepancies could be attributed to the poor knowledge of the absolute DOSs, rather than manifestations of non-ergodicity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to this, other aspects of dissociation kinetics of metal clusters are now modeled with great sophistication using both statistical theories and the methods of molecular dynamics. [39][40][41] …”
Section: Introductionmentioning
confidence: 99%